LEARNER’S EXPECTATION OF ONLINE CLASS MANAGEMENT IN ENGLISH TEACHING AND LEARNING PROCESS - Imro Atus Soliha; Ulil Hidayah; Pratiwi Dwi Warih Sitaresmi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This study inspected student’s expectations in English Language Teaching at the first grade of MAN 2 Probolinggo. The expectation regards the effectiveness of online class management. There were 50 learners asked to fill questionnaires which contained 20 questions appertain to the diverse styles and methods of management techniques. It included intrinsic and extrinsic characteristics, which are often practiced and used by many teachers in an online class. Learners were requested to answer on a 5 dimension scale start from “not important” to “very important” related to what should teachers do in an online class to make learners more understand and enjoy the learning process. Participation was voluntary ask to fill the questionnaires. Unexpectedly, the results showed that online class management is needed for both learners and teachers. Learners were curious whether they were valued and got attention from the teachers and not to hesitate to speak freely in their classroom during the learning process. The authors hope this information can help teachers in arranging their online classes and also having a nice online class with all students.